2013
DOI: 10.1105/tpc.113.117788
|View full text |Cite
|
Sign up to set email alerts
|

TheTrans-Acting Short Interfering RNA3 Pathway and NO APICAL MERISTEM Antagonistically Regulate Leaf Margin Development and Lateral Organ Separation, as Revealed by Analysis of anargonaute7/lobed leaflet1Mutant inMedicago truncatula   

Abstract: Leaf shape elaboration and organ separation are critical for plant morphogenesis. We characterized the developmental roles of LOBED LEAFLET1 by analyzing a recessive mutant in the model legume Medicago truncatula. An ortholog of Arabidopsis thaliana ARGONAUTE7 (AGO7), Mt-AGO7/LOBED LEAFLET1, is required for the biogenesis of a trans-acting short interfering RNA (ta-siRNA) to negatively regulate the expression of AUXIN RESPONSE FACTORs in M. truncatula. Loss of function in AGO7 results in pleiotropic phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 66 publications
6
87
1
13
Order By: Relevance
“…It was subsequently found that AGO7 is preferentially loaded with miR390 and triggers production of tasiRNAs from the TAS3 locus (Garcia et al, 2006;Montgomery et al, 2008). TAS3-derived tasiRNA target AUXIN RESPONSE FACTORS and regulate leaf patterning and lateral organ separation (Montgomery et al, 2008;Zhou et al, 2013). This role of AGO7 appears conserved across plants as it has been also reported from rice (Nagasaki et al, 2007;Shi et al, 2007) and maize (Douglas et al, 2010).…”
Section: Ago7mentioning
confidence: 78%
See 1 more Smart Citation
“…It was subsequently found that AGO7 is preferentially loaded with miR390 and triggers production of tasiRNAs from the TAS3 locus (Garcia et al, 2006;Montgomery et al, 2008). TAS3-derived tasiRNA target AUXIN RESPONSE FACTORS and regulate leaf patterning and lateral organ separation (Montgomery et al, 2008;Zhou et al, 2013). This role of AGO7 appears conserved across plants as it has been also reported from rice (Nagasaki et al, 2007;Shi et al, 2007) and maize (Douglas et al, 2010).…”
Section: Ago7mentioning
confidence: 78%
“…Non-canonical miRNAs were discovered during systematic analyses of small RNAs in different model systems, such as disease models (e.g. Xia et al, 2013) or cultured cells (Babiarz et al, 2008;Babiarz et al, 2011). A good experimental strategy to identify non-canonical miRNAs is a high throughput sequencing analysis of genetic models lacking some of the components of RNA silencing such as Dicer or DGCR8 (Babiarz et al, 2008;Babiarz et al, 2011).…”
Section: Additional Small Rnas Associated With Ago Proteinsmentioning
confidence: 99%
“…For SEM observation, dry mature seeds were cut with a sharp razor blade at the central region. SEM analysis was performed as described previously (24,40). Thirty-six-day-old seeds were used for cryosectioning, as seeds at this stage have suitable hardness for cutting with Cryostat Leica CM 1850 without fixation treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in several genes in the tomato tasiRNA pathway, which are negative regulators of ARF2, 3 and 4, were shown to underlie the tomato 'wiry' syndrome of very narrow leaves with reduced complexity (Lesley and Lesley, 1928;Yifhar et al, 2012). Interestingly, compromised tasiRNA pathway activity in M. truncatula led to a milder phenotype of increased leaf lobing with no effect on the number of leaflets (Zhou et al, 2013), whereas leaf development in Arabidopsis was unaffected (Hunter et al, 2006). Thus, whereas some mechanisms of marginal patterning are conserved among species, others differ substantially.…”
Section: Marginal Patterning In Simple and Compound Leavesmentioning
confidence: 99%